Correlation between strength and flexibility of knee flexors and extensors muscles in youth soccer players - Cursino, Maira Peloggia; Marques, Ana Elisa Zulliani Stroppa; Quatrochi, Hugo Castellon; Navega, Flavia Roberta Faganello; Pedroni, Cristiane Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Soccer is the most played sport in the world and the one that causes more injuries. Imbalance between knee flexor and extensor is the main cause of muscle injuries in soccer players. Objective: The aim of this study was to verify the asymmetry and the correlation between the strength and flexibility of knee flexor and extensor as well as the difference of these variables between the right and left limbs in youth soccer players. Method: The sample consisted of 45 male youth soccer players for at least a year, aged between 13 and 16 years (14.7+0.86). The athletes underwent an assessment of flexibility of the posterior chain through the sit and reach test on Wells’ Bench and an assessment of flexibility of the quadriceps using the Ely’s test, with measurement of passive range of motion by goniometry. The peak of muscle strength was measured using a load cell (EMG  System, Brazil). Results: Data analysis showed difference between the values obtained in the Ely’s test of right and left leg (p=0,03), which did not happen for flexion strength (p=0.45), extension (p=0.41) and H:Q ratio (p = 0.40) when comparing the two members. It was observed a significant negative correlation between the H:Q ratio and the flexibility of the posterior chain test either for the right side (r=-0.40; p=0.006) or left side (r=-0.50; p=0.0004). Also a significant positive correlation was observed between quadriceps strength and flexibility of the posterior chain, both for the right (r=0.31; p=0.03) and the left side (r=0.32; p=0.02). Just for the left side a significant positive correlation was observed when compared the flexor muscle strength with the flexibility of the quadriceps (r=0.30; p=0.03). Conclusion: We conclude from this study that the flexibility of the posterior chain may be related to the strength of the antagonists, however, when the two physical qualities were compared in the same muscles, it showed no correlation.